2000
DOI: 10.1007/s004240000462
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid-induced Ca2+ sensitization of smooth muscle contraction through activation of Rho-kinase

Abstract: Arachidonic acid activates isolated Rho-kinase and contracts permeabilized smooth muscle fibres. Various assays were carried out to examine the mechanism of this activation. Native Rho-kinase was activated 5-6 times by arachidonic acid but an N-terminal, constitutively-active fragment of Rho-kinase, expressed as a glutathione-S-transferase (GST) fusion protein and including the catalytic subunit (GST-Rho-kinase-CAT), was not. GST-Rho-kinase-CAT was inhibited by a C-terminal fragment of Rho-kinase and arachidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 42 publications
4
50
0
Order By: Relevance
“…Studies show that Rho kinase can be activated by Rho as well as by other second messengers such as arachidonic acid and sphingosylphosphorylcholine (2,34). Therefore, we examined whether Rho is involved in activation of Rho kinase in ROS-treated aortic rings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that Rho kinase can be activated by Rho as well as by other second messengers such as arachidonic acid and sphingosylphosphorylcholine (2,34). Therefore, we examined whether Rho is involved in activation of Rho kinase in ROS-treated aortic rings.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2 þ sensitizing mechanisms mediated through arachidonic acid and MAP kinase (Cain et al, 2002) have been reported. Recently, it was reported that arachidonic acid-induced Ca 2 þ sensitization in a-toxin-permeabilized rabbit femoral artery was inhibited by Y-27632 (Araki et al, 2001), suggesting that arachidonic acid activates the rho pathway. MAP kinase was shown to be activated by acetylcholine in canine colonic smooth muscles (Gerthoffer et al, 1996).…”
Section: T Takeuchi Et Almentioning
confidence: 99%
“…Several downstream signaling pathways that inhibit myosin phosphatase activity have been discovered recently, including RhoA/Rho kinase (21), protein kinase C activation of the inhibitory phosphoprotein CPI-17 (22), and arachidonic acid (23,24). In addition, several kinases copurify with myosin phosphatase, including ZIP-like kinase (25), integrin-linked kinase (26), myotonic dystrophy-related kinase (27), and Raf-1 (28), each of which can phosphorylate MBS and inhibit myosin phosphatase activity.…”
mentioning
confidence: 99%